2003
DOI: 10.1002/jbm.a.10160
|View full text |Cite
|
Sign up to set email alerts
|

Increased osteoblast adhesion on titanium‐coated hydroxylapatite that forms CaTiO3

Abstract: CaTiO(3) is a strong candidate to form at the interface between hydroxylapatite (HA) and titanium implants during many coating procedures. However, few studies have compared the cytocompatibility properties of CaTiO(3) to HA pertinent for bone-cell function. For this reason, the objective of the present in vitro study was to determine the ability of bone-forming cells (osteoblasts) to adhere on titanium coated with HA that resulted in the formation of CaTiO(3). To accomplish the formation of CaTiO(3), titanium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 20 publications
3
66
0
2
Order By: Relevance
“…The effect of roughness on cell attachment has been demonstrated before [23,36,43,50,58,61]. It was shown that the surface roughness must be within the scale of the cell to be perceived by the cell, and within this limit, rougher surfaces support the expression of a more differentiated osteoblastic phenotype based on increased alkaline phosphatase activity and osteocalcin production [50].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The effect of roughness on cell attachment has been demonstrated before [23,36,43,50,58,61]. It was shown that the surface roughness must be within the scale of the cell to be perceived by the cell, and within this limit, rougher surfaces support the expression of a more differentiated osteoblastic phenotype based on increased alkaline phosphatase activity and osteocalcin production [50].…”
Section: Discussionmentioning
confidence: 95%
“…It was shown that the surface roughness must be within the scale of the cell to be perceived by the cell, and within this limit, rougher surfaces support the expression of a more differentiated osteoblastic phenotype based on increased alkaline phosphatase activity and osteocalcin production [50]. It was also reported that increased surface roughness, both at the micrometer and at the nanometer levels, without changes in surface chemistry, could promote functions of osteoblasts, leading to new bone synthesis [61]. Most studies, however, have expressed the roughness in terms of R a .…”
Section: Discussionmentioning
confidence: 96%
“…Adhesion is overwhelmingly provided by mechanical clamping of coating particles to asperities of the roughened surface of the metallic substrate. Despite claims that a thin reaction layer of calcium dititanate (CaTi 2 O 5 ) or calcium titanate (perovskite, CaTiO 3 ) exists that will mediate adhesion [35][36][37], experimental evidence of such a reaction layer in as-sprayed coatings is scant or absent. Owing to its thinness, visualization by transmission electron microscopy even at high magnification [20] is hampered by its exiguity owing to the very short diffusion paths of Ca 2+ and Ti 4+ ions, respectively, that render any potential reaction zone extremely thin.…”
Section: Adhesion Strengthmentioning
confidence: 99%
“…20,21) The XRD peaks for HAp particles reveal that HAp particles are incorporated in the oxide film with no loss of crystallinity. Interestingly, CaTiO 3 , which is known to play a key role in the induction of bone-like apatite through the formation of Ti-OH, 19,22,23) was detected as clear peaks. CaTiO 3 is considered to be produced by Ca 2þ ions from HAp being incorporated in Ti substrates by the spark discharge energy.…”
Section: Characterization Of the Anodized Materialsmentioning
confidence: 99%